2019
DOI: 10.46378/irjst.2019.010105
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Quality Characteristics of Bamboo/Cotton Blended Yarns of Rotor and Ring Spun

Abstract: Denim fabrics are in general manufactured by using 100% cotton fibers. A novel attempt has been made by using bamboo/cotton yarns in warp and weft directions to produce denim fabrics using ring yarns in warp and rotor yarns in weft directions. In this research work, bamboo/cotton yarns are manufactured in different blend compositions like 100% bamboo, 100% cotton,70:30, 50:50 and 30:70 ratios. Ne 10 and Ne 16 carded yarns are manufactured from both the ring and rotor spinning systems. The yarns manufactured o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study has reported that fabrics constructed with ring-spun yarns exhibited better moister management, water vapor transmission rate, tensile and tear strength than rotor yarn fabrics. In contrary, rotor yarns have better air permeability, crease recovery and fabric assistance than the ring yarn fabrics (Nagarajan et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study has reported that fabrics constructed with ring-spun yarns exhibited better moister management, water vapor transmission rate, tensile and tear strength than rotor yarn fabrics. In contrary, rotor yarns have better air permeability, crease recovery and fabric assistance than the ring yarn fabrics (Nagarajan et al , 2019).…”
Section: Introductionmentioning
confidence: 99%